SEXUAL ORIENTATION AND GENDER IDENTITIES (SOGI) LAW AND SOCIAL CHANGE (The Pretoria Student Law Review, 2021)
It has been widely acknowledged in the realm of research that Africa is historically a diverse continent for gender identities and sexual orientations and practices. Research conducted through various disciplines depicts accounts of unique bond-friendships and dynamic gender roles that existed openly prior to the introduction of colonial discriminatory laws. With variation in social and legal positions with regard to LGBTQIA+ rights and recognition over time and space, the question is postulated of how the natures of social and legal change affects the relationship between these positions. The adoption of Queer Theory, as a lens of analysis, does not dichotomise the relationship of social and legal changes through a riddle of which came first, but rather acknowledges the domination of prevailing anti-LGBTQIA+ sentiments in colonial governments through the mechanism of law. The embedment of queer phobia into social institutions allowed for its continued existence postindependence through the shift in perspectives and attitudes toward LGBTQIA+ persons by individuals in society. Though individuals and collectives continue advocating for the recognition and realisation of legal rights and protections for LGBTQIA+ persons throughout the continent, varying legitimisation has only been seen in limited countries such as South Africa, Botswana, and Angola.
Keywords: gender identities; sexual orientations and practices; LGBTQIA rights; Queer Theory; anti-LGBTQIA sentiments; colonial governments